2022
DOI: 10.1039/d2sm00841f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the synergistic effect of melt-extension and nanofiller on the crystal–crystal phase transition from form II to I of isotactic polybutene-1

Abstract: New questions and conjectures are raised on the crystal-crystal phase transition of isotactic polybutene-1 (iPB-1) containing nanofiller in the flow field. In this work, we investigate the phase transition from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A homemade two-drum extensional rheometer , was utilized to load the extensional flow field. As shown in Figure a, the sample was fixed to the two gear drums with clamps and was stretched by rotating the gear drums in the opposite direction.…”
Section: Methodsmentioning
confidence: 99%
“…A homemade two-drum extensional rheometer , was utilized to load the extensional flow field. As shown in Figure a, the sample was fixed to the two gear drums with clamps and was stretched by rotating the gear drums in the opposite direction.…”
Section: Methodsmentioning
confidence: 99%
“…2 Therefore, an efficient approach of quickly obtaining a trigonal phase remains a challenge. Previous studies have revealed that II-I phase transition can be accelerated by high pressure, 1,15,16 proper control of temperature, [17][18][19][20] solvent, 21,22 supercritical CO 2 , 16,23,24 blending, [25][26][27][28] change of macromolecular structures, [29][30][31][32][33] application of external forces, [34][35][36][37] etc. Among these methods, introducing the foreign co-units into the main chain of PB is effective to change the molecular structure and tune the crystal polymorphism.…”
Section: Introductionmentioning
confidence: 99%